The Case for CLIL (Transcript of Podcast) - Susan Hillyard (Universidad de La Sabana, 2009)
In this podcast, Susan Hillyard provides a personal reflection on what CLIL means to her as well as the main influences she considers important in the development of CLIL over the years. Key to this understanding of CLIL is also the changing role of English and the fact that the content and language are becoming inextricably linked in the changing educational landscape of the 21st century.